Insiden kegemukan pada masyarakat vegetarian di asrama Sri Sri Radha Vrndavan Candra Singaraja - Made Naradi Kawiyatna; GN. Indraguna; Putu Cintya Denny Yuliatni (Intisari Sains Medis, 2019)
Background: Obesity is one of the health and nutrition problems of the world community, both in developed countries and in developing countries. One effort to solve obesity is being a vegetarian. Vegetarian diet is a diet that only requires vegetable products with or without milk and eggs. This study aims to study the event of obesity in the vegetarian community in the dormitory of Sri Sri Radravanavan Chandra Singaraja.Methods: This type of descriptive research is carried out by using a retrospective approach. Data collection starting from events that have occurred or are ongoing to do a description of general characteristics and specific variables of the study to answer the research objectives. Variables that have been recorded will be determined by the prevalence of hypertension and overweight. The subjects of the study were hypertensive patients in middle-aged with overweight based on data obtained from East Denpasar Puskesmas I. Sampling was done using a random sampling method. the type of research is descriptive study, that means this research only makes a description of the data that has been obtained by using a questionnaire on vegetarians in the dormitory of Radha Vrindavan Candra Singaraja. Data retrieval was taken by the Total Sampling method. Distribution of researcsh variables were BMI, Percent fat and Hip Waist Circumference. 30 samples that meet the inclusion criteria were included in this study.Results: body mass index variables show that in Male as many as 12 samples (80%) were classified as healthy and had an average body mass index (SB) of 22.9 (2.13) kg / m2. In the variable body mass index, 14 of female samples (93.3%) were classified as healthy and had a mean body mass index (SB) of 23.7 (1.63) kg / m2. In Percent Body Fat variables, male shows as many as 4 samples (26.7%) are included in the category of slightly overlap with an average Percent Body Fat (SB) of 15.6 (4.96%). In Percent Body Fat variables, females as many as 11 samples (73.3%) were optimal, with an average Percent Body Fat (SB) of 17.4 (3.24%). In the Hip Waist Ratio variable male as many as 9 samples (60%) were at risk of replacing obesity, with an average Hip Waist Ratio (SB) of 0.9 (0.03%). In the female Hip Waist Ratio variable, 12 samples (80%) were at risk of obtaining mercy with an average Hip Waist Ratio (SB) of 0.87 (0.02%).Conclusions: Based on body mass index, in the male sample it was found that 20% were overweight, while women were only 6.7%. Based on Percent Body Fat, the incidence of obesity was only found in male sex (20%), 13.3% of women included in the slightly overfat category. Based on the Hip Waist Ratio, 80% of women are at risk of obesity, while men are 60%.Latar Belakang: Kegemukan merupakan salah satu masalah kesehatan dan gizi masyarakat dunia, baik di negara maju maupun di negara berkembang. Salah satu upaya mengatasi kegemukan adalah dengan mengatur pola makan vegetarian Vegetarian adalah pola makan yang hanya mengkonsumsi produk nabati dengan atau tanpa susu dan telur. Penelitian ini bertujuan untuk mengetahui kejadian kegemukan pada masyarakat vegetarian di asrama sri sri radha vrndavan candra singaraja.Metode: Jenis penelitian ini deskriptif yaitu rancangan penelitian yang hanya melakukan deskripsi mengenai data yang telah diperoleh yaitu dengan menggunakan kuisioner pada masyarakar vegetarian di asrama ari ari radha vrndavan candra singaraja. Pengambilan data di ambil dengan metode Total Sampling. Distribusi variable penelitian yaitu IMT, Persen lemak dan Lingkar Pinggang Pinggul. 30 sampel yang termasuk kriteria inklusi diikutsertakan dalam dalam penelitian ini.Hasil: laki-laki sebanyak 12 sample (80%) tergolong healty dan memiliki rata-rata Indeks Masa Tubuh (IMT) (SB) 22,9 (2,13) kg/m2. IMT perempuan 14 sample (93,3%) tergolong healty dan memiliki rata-rata IMT (SB) 23,7 (1,63) kg/m2. PLT laki-laki sebanyak 4 sampel (26,7%) termasuk dalam kategori slighty overfat dengan rata-rata PLT (SB) 15,6 (4,96%). Persen Lemak Tubuh (PLT) perempuan sebanyak 11 sampel (73,3%) tergolong optimal, dengan rata-rata PLT (SB) 17,4 (3,24%). RLPP laki-laki sebanyak 9 sampel (60%) beresiko mengalami kegemukan, dengan rata-rata Rasio Lingkar Pinggang Pinggul (RLPP) (SB) 0,9 (0,03%). RLPP perempuan yaitu 12 sampel (80%) beresiko mengalami kegemukan dengan rata-rata RLPP (SB) 0,87 (0,02%).Simpulan: Berdasarkan variabel IMT, pada sampel laki – laki ditemukan 20% yang mengalami overweight, sedangkan perempuan hanya 6,7%. Berdasarkan variabel PLT, kejadian kegemukan hanya ditemukan pada jenis kelamin laki – laki (20%), 13,3% perempuan termasuk dalam kategori slightly overfat. Berdasarkan variabel RLPP, 80% perempuan beresiko mengalami kegemukan, sedangkan laki – laki 60%.